Comparative Study of Greenwashing Practices in Consumer Protection Between Indonesia, the Netherlands, and Singapore - Hariyanto, Helen Hervinia; Tarina, Dwi Desi Yayi (Universitas Muhammadiyah Sidoarjo, 2025)
General background: As global environmental awareness rises, corporations increasingly use sustainability claims to attract consumers, yet many of these claims constitute greenwashing that misleads the public about environmental benefits. Specific background: This practice undermines environmental protection efforts and erodes consumer trust, especially in Indonesia, where legal instruments addressing greenwashing remain limited. Knowledge gap: Previous research has explored corporate responsibility and consumer rights, but few studies have compared cross-country legal protections against greenwashing. Aims: This study analyzes and compares the legal frameworks and enforcement mechanisms for consumer protection against greenwashing in Indonesia, the Netherlands, and Singapore. Results: The findings show that Indonesia relies on general provisions within its Consumer Protection and Environmental Laws, while the Netherlands enforces binding EU directives through strong oversight institutions such as the ACM. Singapore combines the Consumer Protection (Fair Trading) Act with the regulatory authority of ASAS. Novelty: This study introduces a comparative legal analysis highlighting the need for Indonesia to strengthen its regulatory framework and establish a specialized supervisory body for greenwashing cases. Implications: The study contributes to developing more transparent and accountable consumer protection mechanisms that advance global sustainability objectives. Highlights: Highlights gaps in Indonesia’s legal framework on greenwashing. Compares consumer protection systems in Indonesia, the Netherlands, and Singapore. Recommends stronger, specialized oversight for sustainability claims. Keywords: Greenwashing, Consumer Protection, Comparative Law, Sustainability, Regulation